Physico-chemical properties and sensory acceptance of mixed drinks of red cabbage (Brassica oleracea L.) and roselle (Hibiscus sabdariffa L.) extracts - Hani M.N.F.; Zaiton H.; Faridah H.; Norlelawati A. (Universiti Putra Malaysia, 2024)
Indexed by WOS/SCOPUS/ERA/MYCITE